Frequency and risk factors of pressure injuries in clinical settings of affiliated to Tabriz University of Medical Sciences - AhmadMirza Aghazadeh; Mojgan Lotfi; Hossein Asgarpour; Mohammad Khajehgoodari; Afsaneh Nobakht (Wiley, 2021)
Abstract Aim Pressure injuries are considered a common and costly problem in the care of patients. Prevention and identification of risk factors for pressure injuries are very important due to the high cost of treatment and the adverse consequences of pressure injuries. This study aimed to assess the prevalence of pressure injuries and its risk factors in clinical settings of affiliated to Tabriz University of Medical Sciences. Design A descriptive‐analytical study. Methods This study was performed on 200 patients who were selected by random sampling. The data collection tool was a 3‐part questionnaire. Data were analysed using a t test, chi‐square, Fisher's exact test and logistic regression in SPSS v. 24. Results The mean age of the participants was 51.93 (SD 14.99) years. The rate of pressure injuries in this study was 19.5%. The most susceptible area for pressure injuries were sacral (35.89%) and gluteal (20.51%), respectively. The pressure injuries was significantly associated with Braden's criteria, age, disease diagnosis and length of hospital stay (p < .05). But there was no statistically significant difference between sex and incidence of pressure injuries (p > .05).